2014
DOI: 10.1098/rspb.2014.0261
|View full text |Cite
|
Sign up to set email alerts
|

Positive interactions between herbivores and plant diversity shape forest regeneration

Abstract: The effects of herbivores and diversity on plant communities have been studied separately but rarely in combination. We conducted two concurrent experiments over 3 years to examine how tree seedling diversity, density and herbivory affected forest regeneration. One experiment factorially manipulated plant diversity (one versus 15 species) and the presence/absence of deer (Odocoileus virginianus). We found that mixtures outperformed monocultures only in the presence of deer. Selective browsing on competitive do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
39
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 50 publications
7
39
0
Order By: Relevance
“…). Here, the effects on diversity were highly selective, as has been reported elsewhere for deer (Cook‐Patton, LaForgia & Parker ). Many species, other than oak and small subset of native forbs, show little or no evidence of browsing including the exotic dominant grasses and non‐savanna tree species (MacDougall et al .…”
Section: Discussionsupporting
confidence: 71%
“…). Here, the effects on diversity were highly selective, as has been reported elsewhere for deer (Cook‐Patton, LaForgia & Parker ). Many species, other than oak and small subset of native forbs, show little or no evidence of browsing including the exotic dominant grasses and non‐savanna tree species (MacDougall et al .…”
Section: Discussionsupporting
confidence: 71%
“…We observed that intensity of moose browsing not only altered the shape of the relationship between tree growth and tree species richness but also reversed the effects of tree species richness on insect herbivores. Interestingly, the only two previous studies exploring interactions between effects of mammalian herbivores and plant diversity have shown that browsing effects enhance rather than counter the positive effects of plant species (Cook‐Patton, Laforgia & Parker ) and genetic diversity (Parker, Salminen & Agrawal ) on the performance of tree seedlings or herbaceous plants, respectively. Both Parker, Salminen & Agrawal () and Cook‐Patton, Laforgia & Parker () cite browsing selectivity and associational protection as the main mechanisms through which browsing shifted polyculture output to less palatable but high‐performing species or genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, in ecology, there is significant evidence that local, microscopic interactions between and within populations affect properties such as resistance to perturbations, efficiency of resource utilization, rates and yields of biomass production, etc. [24]. All these are macroscopic properties that depend on how the microscopic building blocks (genes, genotypes, and cells) are assembled.…”
Section: Introductionmentioning
confidence: 99%